Ethical Decision Making: Special or No Different? - Elm, Dawn R.; Radin, Tara J. (2012)
Theories of ethical decision making assume it is a process that is special, or different in some regard, from typical individual decision making. Empirical results of the most widely known theories in the field of business ethics contain numerous inconsistencies and contradictions. In an attempt to assess why we continue to lack understanding of how individuals make ethical decisions at work, an inductive study of ethical decision making was conducted. The results of this preliminary study suggest that ethical decision making might not be meaningfully “special” or different from other decision making processes. The implications of this research are potentially significant in that they challenge the fundamental assumption of existing ethical decision making research. This research could serve as an impetus for further examination of whether ethical decision making is meaningfully different from other decision making processes. Such studies could create new directions for the field of business ethics.
Keywords: Qualitative Research; Inductive study; Decision Making; Ethical decision making; Business Ethics